Can Elastography Predict Growth of Incidental Thyroid Nodules? A Pilot Two-Year Follow-Up Study. (September 2016) - Krejbjerg, Anne; Pedersen, Inge Bülow; Laurberg, Peter
The objective of this study was to examine the ultrasonography (US) and ultrasound elastography (USE) features of thyroid incidentalomas in a population exposed to iodine deficiency and to investigate whether baseline elasticity scores (ES) predicted changes in thyroid nodule US characteristics. We conducted a two-year follow-up pilot study of thyroid incidentalomas by US and USE. One sonographer performed the US and USE examination on the same apparatus at baseline and at follow-up. We evaluated 83 incidental thyroid nodules detected in a population study. The follow-up period saw no change in median thyroid nodule diameter ( p = 0.18) or in the prevalence of thyroid nodule US characteristics (hypoechoic: p = 0.05; solid nodule: p = 1.00; microcalcifications: p = 0.55). Individual changes in thyroid nodule diameter (>20%) were seen in 23% (11% had decreased, and 12% had increased in diameter). Changes in ES were frequently observed; 37% changed from ES A + B to ES C + D, and 27% changed from ES C + D to ES A + B. In a multivariate logistic regression model, we found no association between baseline ES and individual changes in nodule size. In an area with mild iodine deficiency and a high prevalence of thyroid nodules, thyroid USE performed on thyroid incidentalomas did not predict individual changes in thyroid nodule size.